THE EFFECT OF SPECIAL PHYSICAL EXERCISES ON DEVELOPING SOME ELEMENTS OF PHYSICAL FITNESS AND BASIC SKILLS AMONG YOUNG FEMALE BASKETBALL PLAYERS - Prof. Dr. Uday Mahmoud Zahmar; Dr. Mustafa Khurshid Ahmed (Galaxy International Interdisciplinary Research Journal, 2022)
To identify the differences between the pre and post tests of the experimental group in some elements of physical fitness and basic skills of (under 18 years old, henceforth U18) young basketball players. Identifying the differences between the post tests of the control and experimental research groups in some elements of physical fitness and basic skills of U18 young female basketball players.